HER2 amplification in colorectal cancer with brain metastasis: A propensity score matching study. (March 2023) - Chen, Po-Chuan; Yeh, Yu-Min; Chu, Chun-Ting; Su, Pei-Fang; Chiu, Pin-Hsuan; Lin, Bo-Wen; Chen, Shang-Hung; Lin, Peng-Chan; Lee, Chung-Ta; Chen, Helen H.W.; Chen, Chien-Chin
Abstract: Background: The association between human epidermal growth factor receptor-2  (HER2) amplification and brain metastasis (BM) in patients having colorectal cancer (CRC) has been suggested but not yet established. This study investigated the expression patterns of HER2, its association with BM, and its prognostic value in patients having CRC. Methods: We retrospectively identified 99 patients having metastatic CRC (mCRC) and BM (the BM cohort) and compared them with a cohort of 249 patients having mCRC and without BM (the stage IV cohort) by propensity score matching. Immunohistochemical studies of HER2 on all available paraffin-embedded tumour samples, either from the primary tumour, the metastasis (brain and/or extracranial sites) or both, were performed and analysed. HER2 fluorescent in situ hybridisation was applied when necessary. The expression of HER2 was compared and correlated with survival. Results: HER2 amplifications were detected in 16 (18.4%) of 87 and 9 (3.6%) of 249 patients who had specimens available in the BM and stage IV cohorts, respectively ( P  < .001). After propensity score matching, HER2 amplification was significantly associated with BM (odds ratio: 5.38, P  = .003). HER2 heterogeneity was frequently observed not only at the single tumour level but also in paired tumour samples. A marginally significant longer survival since BM was found in patients having HER2-amplified mCRC than in those without ( P  = .07). Conclusions: HER2 amplification was significantly associated with BM in patients having mCRC and might have prognostic value for survival since BM. Given the heterogeneity of HER2 expression, the testing of HER2 status on available tissues from both primary and metastatic tumours should be encouraged. Highlights: Propensity score matching examined HER2 amplification and brain metastases. High frequency of HER2 amplification in patients having metastatic colorectal cancer and brain metastasis was demonstrated. Intra-patient heterogeneities of HER2 amplification were observed.